Emotional Awareness Moderates the Association Between Discrimination and Emotional-Behavioral Problems: A Cross-Informant Study in Chinese Rural-to-Urban Migrant Youth. (June 2020) - Lan, Xiaoyu; Scrimin, Sara; Moscardino, Ughetta
The present study used a sample of Chinese rural-to-urban migrants in early adolescence to examine whether emotional awareness (EA) moderated the expected association between status-based discrimination and emotional-behavioral problems and whether patterns of associations differed across informants (self-report vs. teacher-report). A total of 169 migrant early adolescents (46.1% girls, age: 10-13 years) living in Shanghai completed self-report measures of discrimination and emotional-behavioral problems, while self-related and other-related EA were assessed via structured vignettes. Teachers were asked to evaluate their students' emotional-behavioral problems. Linear regression analyses indicated that at high levels of discrimination, adolescents with higher EA-self reported having more emotional-behavioral problems than those with lower EA-self; in addition, adolescents with lower (as opposed to higher) EA-other were rated as more problematic by their teachers. Our findings suggest that school-based prevention or intervention programs may target EA-related abilities to minimize the adverse effects of discrimination on rural-to-urban migrants' socioemotional adjustment.